Analisis Tingkat Kepuasan Pengguna Terhadap Aplikasi Indrive Menggunakan Metode Servqual Dan Importance Performance Analysis (IPA) - Hafidz Aqilla Herlambang; Aries Dwi Indriyanti (CV. SINAR HOWUHOWU, 2026)
The development of ride-hailing services such as inDrive in Surabaya shows a positive growth trend, yet it is still accompanied by user complaints regarding system reliability and application responsiveness. This study aims to analyze the level of user satisfaction with the service quality of the inDrive application in Surabaya City using the Service Quality (SERVQUAL) and Importance Performance Analysis (IPA) methods. This study uses a descriptive quantitative approach with data collected through questionnaires distributed to 105 inDrive users selected using a convenience sampling technique. The conformity level analysis results showed a score of 98.47%, indicating that the service quality is quite good but has not fully met user expectations. Based on the SERVQUAL gap analysis, four dimensions had negative gap values: Reliability (-0.12), Assurance (-0.06), Tangibles (-0.05), and Empathy (-0.05), while the Responsiveness dimension had a positive value (0.01). The mapping results on the IPA Cartesian diagram show that there are four attributes included in Quadrant I (Top Priority) that must be improved immediately, namely service accuracy (RL2), ease of system and driver service (RL4), driver's ability to answer app-related questions (AS3), and alertness in responding to requests (RS4). In conclusion, inDrive needs to prioritize improvements in the reliability and assurance aspects to optimize overall customer satisfaction.